Moderate Temperature Treatment of Gas-Phase Volatile Organic Toluene Using NiO and NiO–TiO2 Nano-catalysts: Characterization and Kinetic Behaviors - Fares Almomani (12585685) (2022)
Abstract For the first time, the potential of Ni/NiO and NiO–TiO2 nano-catalysts for the oxidation of toluene under moderate temperatures was investigated. The nano-catalysts were prepared using the solution combustion synthesis method (SCSM) and the effect of the composition of nano-catalysts, the inlet toluene concentration $$([\text{C}_{7} {\text{H}}_{8}]_{in})$$ ( [ C 7 H 8 ] in ) , the relative humidity (RH), and the temperature on the percentage of toluene conversion ($$\% {\text{TN}}_{Conv.} )$$ % TN C o n v . ) were subsequently examined. Results revealed that the nano-catalysts synthesized with a low fuel-to-metal ratio produced pure NiO, which has significant catalytic activity toward the conversion of toluene. Conversely, the high fuel-to-metal ratio generated a nano-catalysts that contains a mixture of Ni/NiO or pure Ni with low activity toward the conversion of toluene. Adding NiO to TiO2 increased the surface area of the catalyst, augmented the catalyst active sites, enhanced the oxidation of toluene, and increased CO2 selectivity ($${\text{S}}_{{{\text{CO}}_{2} }}$$ S CO 2 ). NiO and NiO–TiO2 nano-catalysts exhibited higher reaction rates, significant catalyst turnover frequency, and low activation energy. The obtained results revealed that the SCSM is a promising synthesis method for producing NiO or NiO–TiO2 nano-catalysts, which can be employed successfully for the removal of toluene from gas streams. Other Information Published in: Waste and Biomass Valorization License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s12649-020-01270-4